Antimicrobial resistance monitoring of commensal Enterococcus faecalis in broiler breeders - Noh, Eun Bi (Poult Sci, 2020)
Enterococcus faecalis (E. faecalis) has rapidly acquired resistance to multiple antimicrobials, and the antimicrobial resistance of E. faecalis from broiler breeders has been implicated in its vertical transmission to their offspring. The objective of this study was to investigate the antimicrobial resistance and genetic diversity of commensal E. faecalis isolated from the broiler breeder farms. Among a total of 229 E. faecalis isolates from 9 broiler breeder farms, the highest resistance rate was observed in tetracycline (78.2%), followed by doxycycline (58.1%) and erythromycin (43.7%), and the prevalence of antimicrobial resistance showed significant differences among the 9 broiler breeder farms (P < 0.05). The tetM gene (77.1%) and ermB gene (85.0%) were detected at the highest levels in 179 TE-and 100 E-resistant isolates, respectively. Twenty-four high-level gentamicin-resistant isolates carried aac(6″)Ie-aph(2″)-la gene, and 9 high-level ciprofloxacin-resistant isolates showed point mutations in both gyrA and parC genes. All high-level gentamicin-resistant or high-level ciprofloxacin-resistant isolates showed one of the two different virulence gene patterns, ace-asa1-efaA-gelE complex or ace-efaA-gelE complex. These results indicate that constant epidemiological monitoring at the breeder level is required to prevent the pyramidal transmission of antimicrobial-resistant E. faecalis.